If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -6n + 3 = -46 Reorder the terms: 1 + 3 + -6n = -46 Combine like terms: 1 + 3 = 4 4 + -6n = -46 Solving 4 + -6n = -46 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -6n = -46 + -4 Combine like terms: 4 + -4 = 0 0 + -6n = -46 + -4 -6n = -46 + -4 Combine like terms: -46 + -4 = -50 -6n = -50 Divide each side by '-6'. n = 8.333333333 Simplifying n = 8.333333333
| 2x+(x+3)=75 | | 7p+26=-32p+-40+6p | | 5(2z+6)=-4(-5-2z)+3z | | z-3z=8z-7-z | | x=8pi-pi | | 5(x+2)=4x-8 | | 5(2n+12)=4n | | 150n-50=n+325 | | 2(-5x+5)=-4x+4 | | [5a^2-20a+20]+[3a+3]=25 | | -84=2(6+8a) | | x+3=(x-3)(x-3) | | 3a-45b*j=2 | | 5x+30=11x+48 | | w+(3+w)=25 | | z-3z=8z-7-2 | | 150n-50=100+325 | | 7x^2+12=25x | | -67+6x=-6(-x+7)-4 | | 4x^2-6x=4x^2-3x-27 | | 7x+10=6x+3 | | -9y^2-6y^2+y^2= | | 7(4y-6)=14 | | 4x-3(0)=17 | | -120x=-60 | | -6g=-30 | | 9=X*44 | | -5(4t-4)+6t=8t-9 | | c+(5+c)=33 | | 8-4(2+l)= | | q-21=-7 | | 0=4(0)+7 |